The Fiber Content, Reduced Sugar and Organoleptic Quality of Nata De Avocado on The Variation Types of Sugar and Nutrition - Desty Sekar Prameswari; Titik Suryani (Quagga: Jurnal Pendidikan dan Biologi, 2026)
Nata is a probiotic food fermented with the starter Acetobacter xylinum bacteria. Avocado has the potential as nata substrate containing carbohydrates, protein, iron, vitamin A, vitamin B and fat. The purpose of this study was to determine the fiber content, reducing sugar and organoleptic quality of nata de avocado on the type variations of sugar and nutrients. This research method was an experiment with Completely Randomized Design (CRD), 2 factors. Factor I: sugar type (G): brown sugar (25 g) and granulated sugar (25 g). Factor II: nutrient type (N): 25% mung bean extract (62.5 ml) and 25% sword bean extract (62.5 ml). The results showed the best fiber levels, reducing sugar and organoleptic quality of nata de avocado were 4.51% and 12.770%, white color, neutral aroma, chewy texture and preferred in the G1N2 treatment (25 g brown sugar and 62.5 ml sword bean extract).